Product Diversification as A Waste Management Strategy in Small-Scale Chemical Industries - Muawiyatu Al-laitsi; Apep Indra Saputra; Syifa Assalafiyah (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
Product diversification involves transforming generated waste into new products with economic value or useful applications. This approach not only reduces the disposed waste volume but also changes the perception of waste from being a source of problems to a potential source for creating added value. This research is a qualitative study using an observational case study approach. Data were collected through in-depth interviews, direct observations, and document review at a small-scale rubber coagulant industry in Musi Rawas. The research findings indicate that CV. KBJA has begun exploring product diversification strategies for handling sulfuric acid waste by converting it into liquid fertilizer. Moving forward, there's a need for enhanced training and education regarding more effective waste management strategies to improve understanding and implementation of new practices. Additionally, collaboration among industries, government, and research institutions is necessary to facilitate the development of this product diversification.